PENGARUH CITRA PERUSAHAAN TERHADAP KEPERCAYAAN KONSUMEN DAN DAMPAKNYA PADA KEPUTUSAN PEMBELIAN ONLINE DI MARKETPLACE SHOPEE DI KABUPATEN BIREUEN - Muhammad Ferdiananda Chadafi; Kamaruddin Kamaruddin (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
Along with the times, technological developments that continue to develop make the rapid dissemination of information entire of society through various media. One of the results is from the field of information technology that has developed through the use of internet technology. The application of internet technology has entered several aspects of life, such as information services, government, education, to trade or business. Before the invention of the internet, humans tended to do various traditional businesses, where buyers and sellers met each other to negotiate and make transactions. The purpose of this research is to see the determination of the company’s image on consumer trust and its impact on online purchasing decisions on marketplace Shopee in Bireuen Regency. Population of this research is all people in Bireuen Regency who shop online on marketplace Shopee. Sample in this research amounted to 130 people. The sampling method using accidental sampling.Data analysis using SEM AMOS program.After regression using Structural Equation Model (SEM).The results showed that the company's image had a significant and positive effect on trust and online purchasing decisions at the marketplace Shopee in Bireuen Regency. Furthermore, trust partially mediates the relationship between company image and purchasing decisions.